2017
DOI: 10.1038/nrneurol.2017.104
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous thrombosis

Abstract: Cerebral venous thrombosis (CVT) is an important cause of stroke in young adults. Data from large international registries published in the past two decades have greatly improved our knowledge about the epidemiology, clinical manifestations and prognosis of CVT. The presentation of symptoms is highly variable in this disease, and can range from a patient seen at the clinic with a 1-month history of headache, to a comatose patient admitted to the emergency room. Consequently, the diagnosis of CVT is often delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
304
1
48

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 324 publications
(358 citation statements)
references
References 135 publications
5
304
1
48
Order By: Relevance
“…Currently many reports showed the important role of AGEs in the pathogenesis of AS [21][22][23]. Related functions mainly include the following contents: Firstly, AGEs may lead to instability and secondary rupture of plaque surface fibrous layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently many reports showed the important role of AGEs in the pathogenesis of AS [21][22][23]. Related functions mainly include the following contents: Firstly, AGEs may lead to instability and secondary rupture of plaque surface fibrous layer.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations include symptoms and body signs of focal cerebral dysfunction, such as cognitive disorder, sensory dysfunction, paralysis, or aphasia. The observation of carotid artery AS plaque is an important indicator for preventing the development of cerebral thrombosis [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of treatment is to stabilize the clot and allow intrinsic fibrinolysis to reduce clot burden. In randomized controlled trials, this treatment has been demonstrated to be safe even in the presence of intracranial hemorrhage [6, 9]. Guideline recommendations suggest the use of unfractionated or low-molecular-weight heparin followed by vitamin K antagonists [6].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, a subset of patients experience progressive sinus thrombosis and clinical deterioration despite systemic heparin therapy [4-6]. In these patients with medically refractory CVT, pharmacological thrombolysis and endovascular techniques, such as aspiration thrombectomy, balloon angioplasty, and mechanical thrombectomy, have been utilized alone or in combination with medical management of raised intracranial pressure (ICP) or decompressive craniectomy to remove thrombosis and optimize edema and improve outcome [7-9]. Surgical management in medically refractory CVT has typically been limited to ICP monitoring and treatment of intracranial hypertension.…”
Section: Introductionmentioning
confidence: 99%